Gender disparity in students' choices of information technology majors - Yu Zhang; Tristen Gros; En Mao (Business Systems Research (BSR), 2021)
Background: The gender disparity in the Information Technology (IT) field has persisted over the years. In 2018, only 27.2% of IT workers were women. Once hired, women face more challenges, and they are leaving the field twice as fast as men are. The misconception that women are weak in tech is one of the root causes of gender disparity issues in IT. Objectives: We examine the gender disparity in students' choices of IT majors, as well as the decision process of Computer Information Systems (CIS) graduates. Methods/Approach: We use the United States public universities' student data from 2010 to 2018. Both the Pooled and the Satterthwaite t-test are used to investigate the gender disparity issue among the students. Results: Our results support our hypothesis that female students are statistically less likely to choose CIS than their male peers are. An additional analysis of students' grades in CIS courses shows that female students perform equally well as male students do. We did not find any evidence that it takes longer for female students to get the CIS degree; however, female students did change their majors more often. Conclusions: Female students tend to avoid IT majors; they often think they may not do well in the courses; however, such an assumption is not true. Our findings provide strategies for university and high school administration to be more proactive in developing recruiting strategies to attract and retain female CIS students.
Keywords: I23; I24; J16; 330; information technology; computer information systems; gender disparity; information technology education